Implementasi Kurikulum 2013 Dalam Pembelajaran Fiqh Ibadah Kelas VII MTS Negeri 2 Surakarta Tahun Pelajaran 2016/2017 - Waesahoh, Miss Nikusmiyah; , Istanto, S. Pd.I., M.Pd (2017)
The curriculum is a container that will determine the direction of education. The implementation of learning process in Curriculum 2013 emphasizes the achievement of attitude, knowledge, and skill. MTs Negeri 2 Surakarta is a school that has implemented Curriculum 2013 in learning Fiqh Ibadah. The implementation of learning Fiqh Ibadah is not only emphasize the theory but also emphasize practice. Teachers must be able to carry out the learning by using a scientific approach as well as practice it in the classroom. Based on the phenomenon above, the researcher is interested to conduct the research entitled The Implementation of Curriculum 2013 in learning Fiqh Ibadah class VII in MTs Negeri 2 Surakarta. The problem statements in this study include: 1) How the implementation of Curriculum 2013 in learning Fiqh Ibadah in MTs Negeri 2 Surakarta class VII academic year 2016/2017? 2) What are the obstacles and solutions in the implementation of Curriculum 2013 on the subjects of Fiqh Ibadah in MTs Negeri 2 Surakarta class VII academic year 2016/2017?. Therefore the objective of the study is to know and describe the implementation, obstacle and solution of Curriculum 2013 in learning Fiqh Ibadah in MTs Negeri 2 Surakarta class VII academic year 2016/2017. This research uses field research method, with qualitative approach, by taking background in MTs Negeri 2 Surakarta. The subjects of this study were principal, teachers, and students. The methods for collecting data used in this study are in-depth interview, observation, and documentation. Data analysis used is descriptive qualitative data analysis. The results of this study can be concluded that the implementation of Curriculum 2013 in learning Fiqh Ibadah class VII in MTs Negeri 2 Surakarta has been running well, this is marked by the implementation of the stage of planning, implementation phase and evaluation phase in accordance with the implementation guidelines Curriculum 2013. Obstacles implementation Curriculum 2013 is the implementation of assessment by teachers, readiness of students and facilities and infrastructure that have not been adequate. The solution includes teachers of Fiqh Ibadah in city-level MGMP activities, facilitating activities related to teacher competency improvement and complementing the means of supporting learning infrastructure.